Diagnosis of Columnar Metaplasia of the Esophageal Mucosa in Patients with Complicated Gastroesophageal Reflux Disease - E. D. Fedorov; A. V. Shidii-Zakrua; L. M. Mikhaleva; K. S. Maslenkina; A. A. Lindenberg; D. E. Seleznev; V. O. Kaybysheva; T. A. Partenadze (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2024)
Aim: to improve methods of diagnostics of esophageal mucosal forms of metaplasia and dysplasia in patients with complicated forms of gastroesophageal reflux disease (GERD) using multidisciplinary approach.Material and methods. Overall, 131 patients aged 18 to 84 years (mean age — 55.8 ± 16.7 years) with confirmed diagnosis of GERD complicated by development of metaplasia of mucosa of distal esophagus were included in retroand prospective study. At the prehospital stage the patients' complaints were estimated, anamnesis was taken. At the first stage of the diagnostic program all patients underwent detailed esophagogastroduodenoscopy in high resolution with white light. The region of esophageal mucosa with signs of metaplasia and determination of its prevalence was examined and evaluated with special attention. Ultrashort segment was revealed in 26 patients, short segment — in 47 patients, long segment of mucosal metaplasia was revealed in 58 patients. Then to reveal the signs of dysplasia we used specifying endoscopic methods: the structure of pitted and microvascular pattern was estimated in narrow spectral mode using BING classification system. If an irregular type of metaplasized epithelium structure was detected in the process of BING assessment, the areas suspicious for dysplasia were marked, followed by aim forceps biopsy from them. The next stage was staining of the metaplasized segment with 1.5 % ethanic acid solution — acetowhitening. PREDICT classification system was used to evaluate the stained mucosal sections with metaplasia. Targeted forceps biopsy was performed from the altered areas that most quickly lost their coloring. The final stage of the diagnostic program in all patients was a forceps biopsy of the mucosa of the metaplasic segment according to the Seattle protocol, which requires increasing the number of fragments as the metaplasic segment lengthens in a “blind” biopsy. The biopsy material was stained with hematoxylin and eosin, and periodic acid Schiff reaction was performed in combination with alcyanine blue according to the standard technique.Results. Endoscopic examination in white light and evaluation of metaplasia extent revealed ultrashort segment (<1 cm) in 26/131 (19.9 %) patients; short segment (1–3 cm) — in 47/131 (35.9 %); long segment (> 3 cm) — in 58/131 (44.3 %) patients. Among the diagnostic techniques used, the BING and PREDICT classifications had the highest accuracy, sensitivity, and specificity (accuracy — 88.9 and 95.3 %, sensitivity — 90.5 and 91.3 %, and specificity — 86.7 and 100 %, respectively), which significantly exceeded the Seattle protocol also used in this work. The results showed a low level of specificity (31.2 %), accuracy (54.5 %), and sensitivity (76.8 %) of the Seattle protocol. The use of BING and PREDICT classifications provided marking of compromised zones, allowing targeted histological sampling.Conclusions. The original study demonstrated the greatest sensitivity, specificity, and accuracy of PREDICT and BING methods in the diagnosis of metaplasia with signs of dysplasia in patients with complicated GERD. It is also important that the use of BING and PREDICT classification systems allows to reduce the number of biopsy samples in comparison with their unreasonably large number according to the Seattle protocol, thereby reducing mucosal and submucosal trauma of the esophagus and the risk of complications.